CSPG4/NG2 transcriptional activity as a prognostic marker of the postoperative clinical course of glioblastoma - А. Ю. Цидулко; В. В. Кобозев; А. М. Волков; Д. В. Костромская; С. В. Айдагулова; Р. С. Киселев; Т. Ю. Прудникова; А. Л. Кривошапкин (Патология кровообращения и кардиохирургия, 2015)
Objective. Glioblastoma is a malignant brain tumor characterized by severe invasive growth and poor prognosis. The expression of different genes is changed in tumors, including gene CSPG4/NG2, which plays a significant role in the proliferation of glioblastoma cells and tumor neovascularization. The objective of our study was to evaluate the possibility of using the above gene as a prognostic marker for glioblastoma. Methods. 8 patients with a diagnosis "glioblastoma" underwent clinical and molecular-biological examination. The tumor samples were fixed in RNA-later (LifeTechnologies, USA). CSPG4/NG2 and CD44 expression was evaluated by real-time RT-PCR with GAPDH as a reference gene. The patients were divided into two groups according to the postoperative survival rate: Group 1 – less than 1 year, and Group 2 – over 1 year after surgery. Results. Molecular biological studies showed a significant 4-fold increase of CSPG4/NG2 expression level in tumors from group 1 as compared to that of group 2 patients. It was also found out that increased CSPG4/NG2 expression in galloping tumors is in positive correlation with an increase in cancer stem-cell marker CD44 expression (Pearson coefficient 0.9514). Conclusion. The data obtained suggest that CSPG4/NG2 is a promising prognostic marker to determine optimal postoperative treatment of patients with glioblastoma.